SendiriUPlan – Financial planning software and systems - Nur Nadiah Salihah, Mat Razali; Fernando, Yudi (2021)
The system financial freedom puzzles will answer every layer of society to achieve financial independence Usually Certified Financial Planner (CFP) will use their company system to convince their customers to start retirement plan This system assist layman to make Do It Yourself (DIY) approach to encourage saving practices in society